Implications for peace and security in South Asia - Jayaraman, T. (2006)
Official India does not admit that the Indo-US nuclear accord by providing greater flexibility to the Indian nuclear programme and to nuclear weapons production, is a threat to peace in south Asia. - Reproduced.
Keywords: India - Foreign relations - United STates; Nuclear weapons